ESL instructors’ practices in the development of Malaysian university students’ sociolinguistic competence in the English language classroom - Abd Rahman, Siti Nadhirah (2022)
Second language learners often lack sociolinguistic competence, especially when it comes to understanding and using language appropriately according to the context and situation, commonly due to the lack to exposure to appropriate language use. This lack in communicative competence could be due to many factors, such as the absence or lack of communicatively competent speakers, lack of language input outside the classroom, or lack of sociolinguistically appropriate language use in the classroom. For second language learners, classroom interaction is where they mostly use the English language. Unfortunately, sociolinguistic competence is not given much emphasis in the classroom despite the language classroom being the most important and abundant form of language input for second language learners. This case study was conducted to explore how instructors create opportunities and use teaching resources to develop Malaysian university students’ sociolinguistic competence for communicative competence in the language classroom. Three ESL instructors who fulfilled the predetermined selection criteria, indicating their expertise and professional practices, were chosen for this study. In-depth interviews and stimulated recalls were conducted to understand how these instructors create opportunities and utilise teaching resources in the classroom in developing their students’ sociolinguistic competence. Aside from document analysis of the teaching resources, focus group discussions have also been conducted with nine first year university students to support the findings. The theories and concepts that are referred to in guiding this study and its findings are Vygotsky’s sociocultural theory (1978), Halliday’s theory of context (1971) and Hymes’ concept of communicative competence (1967). The findings reveal several themes in the instructors’ creation of opportunities for the development of sociolinguistic competence, including considering students’ context for meaningfulness and authenticity, explicitly teaching sociolinguistic variations, and developing students’ sociolinguistic competence through classroom interaction. Three themes have been reported for the instructors’ use of teaching resources in developing students’ sociolinguistic competence, namely using videos of native speakers, using other students’ work as a teaching resource, and using resources in developing students’ sociolinguistic competence through classroom interaction. A framework of the instructors’ practices for developing sociolinguistic competence in the ESL classroom has also been developed based on the themes found in this study. It can be concluded that the Malaysian ESL instructors in this study created opportunities as well as utilised teaching resources to develop first year university students’ sociolinguistic competence, and it is hoped that other instructors and curriculum designers can gain insights from this study.